2016
DOI: 10.1186/s12933-016-0361-1
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead box transcription factor 1: role in the pathogenesis of diabetic cardiomyopathy

Abstract: Diabetic cardiomyopathy (DCM) is a disorder of the heart muscle in people with diabetes that can occur independent of hypertension or vascular disease. The underlying mechanism of DCM is incompletely understood. Some transcription factors have been suggested to regulate the gene program intricate in the pathogenesis of diabetes prompted cardiac injury. Forkhead box transcription factor 1 is a pleiotropic transcription factor that plays a pivotal role in a variety of physiological processes. Altered FOXO1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 138 publications
1
66
0
2
Order By: Relevance
“…Recently, it was found that miRNAs mediated the benefits of exercise and bariatric surgery to the heart in diabetic/prediabetic patients, and the decreased circulating miR-21 were restored after bariatric surgery or physical activity [25, 29]. Moreover, upregulation of miR-21 or downregulation of its targets could lead to diabetic cardiac dysfunction [3032]. Therefore, miR-21 might play important roles in diabetic cardiomyopathy, and it may be a new therapeutic target for metabolic diseases such as T2DM and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was found that miRNAs mediated the benefits of exercise and bariatric surgery to the heart in diabetic/prediabetic patients, and the decreased circulating miR-21 were restored after bariatric surgery or physical activity [25, 29]. Moreover, upregulation of miR-21 or downregulation of its targets could lead to diabetic cardiac dysfunction [3032]. Therefore, miR-21 might play important roles in diabetic cardiomyopathy, and it may be a new therapeutic target for metabolic diseases such as T2DM and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of FoxO transcription factors can protect against microglial cell demise during oxidative stress (57) and Aβ exposure (58), promotes the protective effects of metabotropic glutamate receptors (59), increases neuronal cell survival through nicotinamide adenine dinucleotide (NAD + ) precursors (60), enhances survival with growth factors (61), such as erythropoietin (EPO) (30, 40, 43, 62) and neurotrophins (6365), and can lessen metabolic and vascular disease (66). Work has suggested that some antipsychotics, such as clozapine, may function through FoxO inhibition to protect against apoptotic neuronal cell loss (67).…”
Section: Foxo Transcription Factors and Cell Deathmentioning
confidence: 99%
“…Inhibition or loss of FoxO activity usually improves cell survival during apoptotic cell injury. Blockade of FoxO transcription factor activity can protect against microglial cell demise during oxidative stress (71) and Aβ exposure (208), foster the protective effects of metabotropic glutamate receptors (209), increase neuronal cell survival through nicotinamide adenine dinucleotide (NAD + ) precursors (210), raise survival with growth factors (211), such as erythropoietin (EPO) (150, 212214) and neurotrophins (215217), and lessen metabolic and vascular disease (218). Antipsychotics, such as clozapine, may function through FoxO inhibition to protect against apoptotic neuronal cell loss (219).…”
Section: Foxo Transcription Factorsmentioning
confidence: 99%